Pengaruh Pendidikan Orang Tua dan Gender terhadap Kemampuan Berpikir Kritis Anak Usia 5-6 Tahun - Cahaya, Cahaya; Bonita, Mahmud; Sutra Awaliyah, Darfin; Nidha Eka Restuti, Munawir (Ihya Ulum: Early Childhood Education Journal, 2024)
Knowing the factors that contribute to students' critical thinking skills will help teachers design inclusive strategies, methods and approaches to improve children's critical thinking skills. The purpose of this study was to determine the effect of parental education and student gender on the critical thinking skills of children aged 5-6 years. Quantitative research approach with quasi-experiment 2x2 factorial design 2-way analysis. The research location is Aisyiyah Mamajang Kindergarten, Makassar City which is based on indicators of critical thinking ability. The collected data were analyzed with parametric statistics with prerequisite tests of normality test, homogeneity test, and hypothesis testing with Two-Way ANOVA. The results showed that the last level of parental education had a significant effect, gender had no effect, there was no interaction between the last level of parental education and gender on the critical thinking skills of children aged 5-6 years.